Meet me by the fountain an inside history of the mall - Lange, Alexandra 1973- (Bloomsbury Publishing, 2022)
An entertaining and evocative stroll through the rise, fall, and ongoing reinvention of malls, which proved to be a powerful draw for creative thinkers including Joan Didion, Ray Bradbury, and George Romero, chronicles how the design of these marketplaces played an integral role in cultural ascent
Keywords: Geschichte 1950-2020; Marktplatz; Architektur; Passage; Einkaufszentrum; USA; Shopping malls / United States / History; Shopping centers / United States / History; Shopping malls / Social aspects; Informational works